Entrepreneurship and the Family Compact: York-Toronto, 1822-55 - Baskerville, Peter (Urban History Review / Revue d'histoire urbaine)

(untitled) (Urban History Review / Revue d'histoire urbaine, 1981)
Through an examination of banking and railway activities, this paper charts the changing nature of entrepreneurship in York-Toronto between 1822 and 1855. It is suggested that the entrepreneurial behaviour of the Compact is best understood through a socio-cultural, rather than a simple economic perspective. The concept, entrepreneurship, should be regarded as time and culture bound. The common argument that members of the Family Compact failed as entrepreneurs, can, then, be refined. While the Compact's perception of success differed from that of its successors and, in some cases, from that of its contemporaries in other cities, that elite was equally active in crucial areas of business development. The activity of leading Compact members and their perceptions of development conditioned Toronto's evolution as a city in the years under review.